Grain refinement of Ti6Al4V by incorporating in-situ TiB nanowhiskers in laser melting deposition - Fu, Ke (2024)
One of the known problems in laser melting deposition (LMD) of alloys is columnar grain morphology and large grain size. Adding reinforcements is generally suggested as a viable approach to tailor the microstructure and enhance mechanical properties. However, quantitative relationships between grain morphology and reinforcement content are sparsely available. In this study, TiB2 particles with different weight ratios were applied in the LMD of Ti6Al4V alloy to investigate its impact on grain refinement. It shows that the increasing TiB2 content enhances the equiaxed grain growth from epitaxial growth and reduces the grain size. A linear function between decreasing grain size and the inverse of the growth restriction factor originating from TiB2 content was obtained. This was attributed to the heterogenous nucleation of in-situ TiB nanowhiskers that promoted the refinement of α lath and prior β grain. The results shed new light on controlling grain morphology and predicting grain size by mixing ceramic-metal materials in LMD additive manufacturing.